2019
DOI: 10.1080/17445647.2019.1595753
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and paleo-ice content of rock glaciers in the southeastern Alps (NE Italy – NW Slovenia)

Abstract: Rock glaciers in the southeastern Alps of Slovenia and Italy have been mapped in detail using high resolution digital elevation model and orthophotos, supported by field-based observations. A total of 52 rock glaciers with an area of 3.40 km 2 have been delineated on a rock glacier map, divided in 18 sections at a scale of 1:15,000. Several geometrical parameters of rock glaciers have been calculated and their activity degree has been inferred. 90% of rock glaciers have been classified as relict, while the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…towards the south with Slovenia and Italy is worth pursuing. Boccali et al (2019) reported 52 mainly relict rock glaciers (88 % relict) and Colucci et al (2016) 66 protalus ramparts (16 of them likely still active) from the north-eastern-most region of Italy (Friuli Venezia Giulia region) and Slovenia. More importantly, for South Tyrol Bollmann et al (2012) reported 1467 rock glaciers, of which 294 are intact and the remaining 80% of the rock glaciers are relict.…”
Section: Discussionmentioning
confidence: 99%
“…towards the south with Slovenia and Italy is worth pursuing. Boccali et al (2019) reported 52 mainly relict rock glaciers (88 % relict) and Colucci et al (2016) 66 protalus ramparts (16 of them likely still active) from the north-eastern-most region of Italy (Friuli Venezia Giulia region) and Slovenia. More importantly, for South Tyrol Bollmann et al (2012) reported 1467 rock glaciers, of which 294 are intact and the remaining 80% of the rock glaciers are relict.…”
Section: Discussionmentioning
confidence: 99%